An Exploratory Evaluation of the Utility of Transcriptional and Urinary Kidney Injury Biomarkers for the Prediction of Aristolochic Acid–Induced Renal Injury in Male Rats. (May 2014) - Fuchs, T. C.; Mally, A.; Wool, A.; Beiman, M.; Hewitt, P.
The predictive value of different urinary and transcriptional biomarkers was evaluated in a proof-of-principle toxicology study in rats using aristolochic acid (AA), a known nephrotoxic agent. Male Wistar rats were orally dosed with 0.1, 1, or 10 mg/kg for 12 days. Urine was collected on days 1, 5, and 12 over 24 hours. Gene expression analysis was also conducted using quantitative real-time polymerase chain reaction and Illumina whole-genome chips. Protein biomarkers (Kim-1, Timp-1, vascular endothelial growth factor, osteopontin, clusterin, cystatin C, calbindin D-28K, β2-microglobulin, α–glutathione S-transferase, GSTY1b, RPA-1, and neutrophil gelatinase-associated lipocalin) were measured in these urine samples. Treatment with AA resulted in a slight dose- and/or time-dependent increase in urinary β2-microglobulin, lipocalin 2, and osteopontin before an increase in serum creatinine or serum urea nitrogen was observed. A strong decrease in urinary calbindin D-28K was also detected. The Compugen Ltd. prediction model scored both the 1- and 10-mg/kg AA dose groups as positive for nephrotoxicity despite the absence of renal histopathological changes. In addition, several previously described transcriptional biomarkers were identified as early predictors of renal toxicity as they were detected before morphological alterations had occurred. Altogether, these findings demonstrated the predictive values of renal biomarkers approved by the Food and Drug Administration, European Medicines Agency, and Pharmaceuticals & Medical Devices Agency in AA-induced renal injury in rats and confirmed the utility of renal transcriptional biomarkers for detecting progression of compound-induced renal injury in rats. In addition, several transcriptional biomarkers identified in this exploratory study could present early predictors of renal tubular epithelium injury in rats.